Membedah Kedudukan Maqashid Syariah Dalam Fatwa MUI Tentang Jual Beli Emas Secara Tidak Tunai Menurut Teori Pendekatan Sistem Jasser Auda - Muhamad Izazi Nurjaman (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
This study describes a discussion about dissecting the position of maqashid syari'ah in the provisions of the MUI fatwa regarding the sale and purchase of gold without cash according to the theoretical perspective of the Jasser Auda system approach. By using the literature study method to collect factual information on theme or topic to be or is being researched. This research tries to explain the fact that the systems approach theory echoed by Jasser Auda, is not only a standard theory but an elastic theory. That is, it can be implemented in legal provisions by means of a surgical process through the application of the six element method which is the criteria. So that the position of the maqashid of sharia can be found its position and of course the legal provisions can be enforced in people's lives to a wide range. Indirectly, the theory of Jasser Auda's system approach is a tool or scale in dissecting the position of maqashid sharia against the legal provisions that have been set or will be enforced.